2016
DOI: 10.1098/rsos.150643
|View full text |Cite
|
Sign up to set email alerts
|

From tissue to silicon to plastic: three-dimensional printing in comparative anatomy and physiology

Abstract: Comparative anatomy and physiology are disciplines related to structures and mechanisms in three-dimensional (3D) space. For the past centuries, scientific reports in these fields have relied on written descriptions and two-dimensional (2D) illustrations, but in recent years 3D virtual modelling has entered the scene. However, comprehending complex anatomical structures is hampered by reproduction on flat inherently 2D screens. One way to circumvent this problem is in the production of 3D-printed scale models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 21 publications
(51 reference statements)
1
21
0
Order By: Relevance
“…As a remedy, 3D virtual models can now also be made accessible to dental students as custom-made and scaled physical objects through additive manufacturing (AM), thus providing students with a genuinely 3D interpretive experience [106,107]. AM is a process by which different types of material can be added layer-by-layer to produce a 3D object [108] and is increasingly being used in the life sciences [109][110][111].…”
Section: Additive Manufacturing Of Three-dimensional Human Tooth Modelsmentioning
confidence: 99%
“…As a remedy, 3D virtual models can now also be made accessible to dental students as custom-made and scaled physical objects through additive manufacturing (AM), thus providing students with a genuinely 3D interpretive experience [106,107]. AM is a process by which different types of material can be added layer-by-layer to produce a 3D object [108] and is increasingly being used in the life sciences [109][110][111].…”
Section: Additive Manufacturing Of Three-dimensional Human Tooth Modelsmentioning
confidence: 99%
“…The uses of 3-D models have made significant changes in the way science is done. For instance, specimens in the past were analyzed in large part through standard, 2-D photographs (Lauridsen et al, 2016). Thanks to 3-D data available today, not only do scientists have the opportunity to produce high fidelity descriptions, but K-12 students can also learn complex concepts, e.g., evolution and extinction, by visually analyzing changes that occur over time (Boyer et al, 2017).…”
Section: Implementing 3-d Scanning Printing and Paleontology In K-12mentioning
confidence: 99%
“…Physical 3D models possess several advantages over virtual and illustrated models as they allow learners to "see with their hands" [5]. This tangibility translates to a strong preference for 3D models among students and researchers alike [6]. Khot et al concluded that physical models are more effective in student learning than computer-based modalities such as Key View (photographed views of a plastic model in a PowerPoint presentation) and virtual reality (3D color image reconstruction from CT) for the study of pelvic anatomy [7].…”
mentioning
confidence: 99%
“…In anatomy, sandstone binder-jetting was used to replicate specimens like a portion of a fossilized hydrosaur femur [6] from overlapped photography and a full-size colored replica of a cadaveric upper limb [18] from CT. Cadaveric reproduction with binder jetting in full color also facilitated the creation of a human head, neck, and orbital model with data collected from a 3D scanner to provide a haptic experience for training ophthalmologists [19]. Additionally, it was used to create a color-coded model depicting the anuran outflow tract of a cane toad heart to demonstrate the use of full-color printing in reproducing complex anatomy [6].Traditionally, researchers achieve color assignment for a 3D print by separating a dataset into multiple files through segmentation of different voxel values (in units of density or intensity). This process historically restricted printing to heterogeneous tissues with significant density differences to enable separate pieces to be produced with corresponding colors.…”
mentioning
confidence: 99%
See 1 more Smart Citation